(untitled) (Journal of Decolonising Disciplines, 2021)
In order to know how to change, one must be able to acknowledge what one does not know. The curriculum cannot be decolonised if those who manage its very problematic existence do not know, understand, or exhibit an inclination towards what needs to be transformed and what needs to be decolonised. This is because no effort is then made to acquire the necessary skills, approaches or knowledge. Central to knowledge production of relevance is the development of a critical consciousness and a recognition that education is politics, where the decolonisation process is imagined, whilst being cognisant of the purpose of and approach to knowledge. Ideologies, pedagogy and societal visions are then shaped because change and adaptation are necessary for survival and relevance. This paper examines these issues by referencing personal experiences during the #FMF protests at the University of Pretoria (UP) and the blossoming of intellectualism, which had been aborted in many instances by a corporate university that sought subservience and sycophancy through processes such as gatekeeping. The intellectual response has often been silence, and the questionable claim that ‘we are transforming’. A robust intellectual project should be in defence of human dignity where academia and the academic work for the greater good of the public makes it relevant.